Group Imagery Rescripting on Childhood Memories Delivered via Telehealth: A Preliminary Study - Tenore, Katia; Mancini, Alessandra; Luppino, Olga Ines; Mancini, Francesco (Frontiers in Psychiatry, 2022)
Background: Imagery Rescripting (ImR) has proven to be effective in the treatment of different mental disorders as an integral part of broader clinical protocols or as a standalone technique. ImR has also been successfully incorporated as part of group Schema Therapy treatment, but, to the best of our knowledge, it has never been assessed as standalone technique in a group setting. Aim: In this study we focused on ImR delivered via telehealth in groups and we aimed to assess whether group ImR is effective in responding to basic emotional needs, in changing participants’ affective state, and in reducing dysfunctional beliefs. We also wanted to assess whether memory realism is associated with a greater effectiveness of the technique. Method: 52 participants were presented with 3 ImR sessions on childhood memories related to the current dysfunctional belief that elicited more suffering. Results: the technique was effective in facilitating the retrieval of a memory in almost the entire sample (range 92.3-100%). Overall, memory realism values (level of vividness, ability to immerse and participants’ distance from the images) were high in all three sessions. Almost all participants reported having their needs met during ImR (89.7%). Importantly, need satisfaction was associated with the ability to immerse in the image. Additionally, the intensity of the dysfunctional belief decreased significantly from pretest to Session 3. The technique also changed the affective state, reducing arousal. Crucially, we also observed a general reduction in shame levels from the first to the third session. Conclusions: a telehealth delivered ImR group intervention on childhood memories produces cognitive and emotional improvement. Along with the ability to satisfy the patient’s basic emotional needs, the technique seems to be effective in modifying maladaptive beliefs incapsulated in memory.